Wall construction process at Simfoni West Taman Tunku Intan Safinaz / Muhammad Iqbal Zamani Muhamad Narzri - Muhamad Narzri, Muhammad Iqbal Zamani (Universiti Teknologi MARA, Perak, 2022)
Wall is a structural element which divides the space (room) into two spaces (rooms) and provides safety and shelter. Generally, the walls are differentiated as two types of outer-walls and inner-walls. Outer-walls gives an enclosure to the house for shelter and inner-walls helps to partition the enclosure into the required number of rooms. Inner walls are also called as Partition walls or Interior Walls and Outer walls are also called as Exterior walls. Walls are constructed in different forms and of various materials to serve several functions. Exterior walls protect the building interior from external environmental effects such as heat and cold, sunlight, ultraviolet radiation, rain and snow, and sound, while containing desirable interior environmental conditions. Walls are also designed to provide resistance to passage of fire for some defined period, such as a one hour wall. Walls often contain doors and windows, which provide for controlled passage of environmental factors and people through the wall line